Disposition of N-methyl-[ring-3,5-3H]tyramine in rabbits and mice - Hai Hua; Guo Zhao-gui; Wang Ji-ming (Acta Pharmacologica Sinica, 2016)
Disposition of N-methyl-[ring-3,5-3H]tyramine in rabbits and mice Hua HAI%Zhao-gui GUO%Ji-ming WANG After iv bolus injection of N-methyl-[ring-3,5-3H] tyramine ([3H]MT) 14.8 MBq/kg in rabbits, the plasma concentration-time data was found to be in accordance with the 2-compartment model. The pharmacokinetic parameters were: T1/2 alpha = 0.3 min, T1/2 beta = 5.6 min, K12 = 0.69/min, K21 = 0.21/min, K10 = 1.6/min, VC = 0.4 L/kg, Cl = 0.62 L/kg.min-1. [3H]MT was taken up by organs rapidly and extensively. Two min after administration, a large amount of radioactivity was detected in every organ sampled. The highest amounts were in the kidney and liver, followed by lung, small intestine, heart, skeletal muscle, spleen, brain and fat. The drug was metabolized extremely fast in vivo. The metabolites were found in the plasma chromatogram just 0.5 min after dosing, while over 80% were found in the urine within 1 h. After a 1 h collecting period, the radioactivity recovered in the urine amounted to 79% of the injected dose. By the end of a 6 h collection, almost no drug was detected in the body.